Fuel Wood Systems: Reduction of Greenhouse Gas Emissions (Global Journal of Science Frontier Research, 2020)
Fuel wood systems offer significant possibilities for reducing greenhouse gas emissions when bio-energy replaces fossil fuel in energy production. This research paper provide analysis of calorific value, wood density, moisture content and ash content of commonly used fuel woods in Girei local government area of Adamawa state-Nigeria to determine the fuel-woods which are suitable as energy source. Nine (9) commonly used wood species of interest were selected for test evaluation. Test result show that Tamarindus Indica, Dalbergia Melanoxylon and Prosopis African have relatively high wood density, high calorific value and low percentage ash content when combusted. Their low ash content is also desirable as fuel since only non-significant part of the volume cannot be converted into useful energy. These wood species should be planted as a source of fuel-wood while efficient wood burning stoves should be develop and adopted in local communities. It is recommended that thermal test performance and emission characteristics of these wood species should be conducted.
Keywords: calorific value; wood density; ash content; moisture content; greenhouse gas emissions